Millions Owe Trillions: Uneven Geographies and Topologies of the Student Debt Crisis in the United States - Harris, Dylan M. (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Millions of students in the United States are saddled with trillions of dollars in debt. The debt crisis is a behemoth, though, importantly, it is not monolithic. Experiences of student debt are unequal and uneven, and it is critical to study them as such to address them. There are many organizations bringing attention to the student debt crisis; however, there are surprisingly few institutions dedicated to studying it. Further, there are few studies that link the student debt crisis to other competing, nested crises of the present (e.g., climate change). Using theories of debt and indebtedness to contextualize the student debt crisis, this paper utilizes auto-ethnographic accounts of student debt – as a student debtor and faculty member – and ‘gray literature’ (reports, policies, and statistics) to highlight and analyze the uneven geographies of student debt in the US. The aim of this paper is to argue that a geographic perspective is generative for studying student debt because it allows for a more nuanced understanding of where and why student debt exists and persists with the intention of complementing ongoing activism to abolish student debt. This paper concludes with four potential pathways for future geographic research on student debt and a call for action.